2012
DOI: 10.1186/1556-276x-7-184
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring of polar and nonpolar ZnO planes on MgO (001) substrates through molecular beam epitaxy

Abstract: Polar and nonpolar ZnO thin films were deposited on MgO (001) substrates under different deposition parameters using oxygen plasma-assisted molecular beam epitaxy (MBE). The orientations of ZnO thin films were investigated by in situ reflection high-energy electron diffraction and ex situ X-ray diffraction (XRD). The film roughness measured by atomic force microscopy evolved as a function of substrate temperature and was correlated with the grain sizes determined by XRD. Synchrotron-based X-ray absorption spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…6 Al doped samples shows the appearance of Zn 3d character in O 2p-Zn hybridized states [33]. Feature D which is diminishing in Al doped samples is signature of O pz orbital's [34]. Shift of absorption edge towards higher energy infers the upward shifts of conduction band which is signature of increase of band gap.…”
Section: Resultsmentioning
confidence: 93%
“…6 Al doped samples shows the appearance of Zn 3d character in O 2p-Zn hybridized states [33]. Feature D which is diminishing in Al doped samples is signature of O pz orbital's [34]. Shift of absorption edge towards higher energy infers the upward shifts of conduction band which is signature of increase of band gap.…”
Section: Resultsmentioning
confidence: 93%
“…As previously reported, the ZnO growth orientation can be altered by different growth conditions or substrates [ 15 , 27 , 39 ]. In this work, the use of hexangular MgO(111) substrates leads to a single growth orientation, which is consistent with the previous expression of the rotational symmetries of the substrate and epilayer, as determined by the formula [ 44 ]: , where N denotes the number of rotation domains in the epilayer; n and m denote the rotational symmetries of the substrate (MgO(111) plane) and epilayer (ZnO(0001) plane), respectively; and lcm ( n , m ) denotes the least common multiple of n and m .…”
Section: Discussionmentioning
confidence: 92%
“…Various ZnO nanostructures, such as 1D nanobelts [ 2 ], nanowires [ 3 ], nanopoints [ 4 ], nanorods [ 5 ], nanocables and nanotubes [ 6 ], 2D nanowalls [ 7 ], and 3D nanotowers [ 8 ], have been successfully synthesized. The morphologies and optoelectronic properties of ZnO nanostructures and ZnO films are controlled by adjusting their preparation conditions [ 8 27 ]. The crystallinities and morphologies of ZnO-based films have been the focus of many studies [ 9 , 11 , 12 , 15 , 16 , 19 , 21 , 23 25 ], as these properties play important roles in device applications.…”
Section: Introductionmentioning
confidence: 99%
“…The different atomic crystal structures for polar and nonpolar ZnO in terms of various bond lengths and symmetries as well as the intrinsic built-in electric field existing only for polar ZnO induce significant influences on the physical properties and device applications. For instance, the electronic conductivity (Maki et al, 2003), the incorporation of impurities (Li et al, 2000) and the thin-film deposition conditions (Zhou et al, 2012) have been shown experimentally to have a strong dependence on the surface polarity, which are further addressed by theoretical calculations (Wang et al, 2005;Gasset et al, 1991;Allen et al, 2009;Yang et al, 2009;Williams et al, 2011). However, a comprehensive understanding of the electronic structure variations upon doping with different surface polarity is still lacking, which will be addressed in the present work using synchrotron-based frontier spectroscopic techniques.…”
Section: Introductionmentioning
confidence: 95%